The role of organizational climate on employee performance: An empirical analysis in the industry sector - Sornnoei, Ekkachai; Potivichayanont, Kanjana; Nakaumka, Neeranuch (Journal of MCU Phetchaburi Review, 2026)
The objectives of this research are 1) study the level of work performance and organizational atmosphere, and 2) study the influence of organizational atmosphere on employee work performance. A questionnaire was used to collect data from 232 employees at the Silathaveechok Stone Quarry, Phetchabun Province. Statistical methods used included frequency, percentage, standard deviation, and multiple regression analysis. The research findings revealed that 1) organizational atmosphere and performance, both overall and in specific aspects, were at a high level, and 2) organizational atmosphere, including organizational structure, accountability, warmth, support, and risk, significantly affected performance at the 0.05 level. The research can predict operational efficiency with 88.80% accuracy. The management of Silachok Stone Quarry can use the research findings to plan strategies for improving the organizational structure. This will enable employees to perceive the benefits of the facilities provided within the organization, leading to improved work efficiency.